Object oriented sparse linear solver component for power system analysis - Mokhlis, Hazlie; Nor, K.M. (IEEE, 2003)
Thls paper describes the develvpment of a sparse linear solver component for solving linear equation In power system analysis. The solver Is developed Into a component by using Object Oriented Programming and Component Based Development methodologies. This component Is then Integrated with the load flow and fault analysis components as power system analysis software. By developing the solver and the power system analyses Into a different component, the engineering analysis becomes Independent from the sparse linear solver. Therefore, the solver can be replaced with other solver, whlth may be proprietary code, or when better or Improved solver becomes available In future. The replacement will not cause any need to modify the load flow and fault analyslsÂ·components. By using Component OilSI'd Development, the software becomes flexible to be updated alad ex tended.